Change and continuity in displacement and response - Hastie, R (Refugee Studies Centre, University of Oxford, 2012)
For 25 years Forced Migration Review has tracked the disasters and crises, concerns and responses to forced migration, from Vietnamese boat people to Syrian refugees. So what has changed and where do we go in the next 25 years?